Do Curriculum-Based Measures Predict Performance on Word-Problem-Solving Measures?. (June 2015) - Sisco-Taylor, Dennis; Fung, Wenson; Swanson, H. Lee
This study examined whether curriculum-based measures (CBMs) of math word-problem contributed unique variance in predictions of performance on high-stakes tests, beyond the contribution of calculation and reading skills. CBMs were administered to a representative sample of 142 third-grade students at three time points. Results indicate that problem-solving CBMs uniquely predicted a problem-solving composite measure and the California Standardized and Reporting test, and were able to discriminate students at risk and not at risk for math difficulties. Implications for practice are discussed.